2021
DOI: 10.1111/jdv.17094
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab therapy of atopic dermatitis of the elderly: a multicentre, real‐life study

Abstract: Background Treatment of moderate‐to‐severe atopic dermatitis (AD) in the elderly may be challenging, due to side‐effects of traditional anti‐inflammatory drugs and to comorbidities often found in this age group. Furthermore, efficacy and safety of innovative drugs such as dupilumab are not yet well known. Objectives A multicentre retrospective, observational, real‐life study on the efficacy and safety of dupilumab was conducted in a group of patients aged ≥65 years and affected by severe AD. Their main clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 30 publications
7
64
1
5
Order By: Relevance
“…5 Elderly-type AD (AD in patients aged ⩾60 years) has been suggested to be a distinct age-related phenotype alongside previously recognized infantile, childhood, and adult phenotypes. [5][6][7]125 As in adult-type AD, lichenified lesions are common, but tend to be localized to the cubital and popliteal extensor areas rather than the flexural areas, as is typical of adult-type AD. 5,126,127 Three forms of elderly-type AD are apparent -elderly onset, relapsing, and continuous -and are subdivided by age at onset.…”
Section: Morphologic Ad Phenotypesmentioning
confidence: 99%
“…5 Elderly-type AD (AD in patients aged ⩾60 years) has been suggested to be a distinct age-related phenotype alongside previously recognized infantile, childhood, and adult phenotypes. [5][6][7]125 As in adult-type AD, lichenified lesions are common, but tend to be localized to the cubital and popliteal extensor areas rather than the flexural areas, as is typical of adult-type AD. 5,126,127 Three forms of elderly-type AD are apparent -elderly onset, relapsing, and continuous -and are subdivided by age at onset.…”
Section: Morphologic Ad Phenotypesmentioning
confidence: 99%
“…Real-world evidence of the effectiveness and safety of dupilumab for atopic dermatitis Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 (Ariëns et al, 2020, Ariëns et al, 2021, Faiz et al, 2019, Fargnoli et al, 2020, Fargnoli et al, 2019, Jang et al, 2020, Jo et al, 2020a, Kreeshan et al, 2021, Matsutani et al, 2020, Nettis et al, 2020b, Nettis et al, 2020c, Olesen et al, 2019, Patruno et al, 2021a, Patruno et al, 2021b, Quint et al, 2020, Ribero et al, 2020, Sears et al, 2020, Tauber et al, 2019, Uchida et al, 2021, Uchida et al, 2019. Patruno et al reported the effectiveness and safety of dupilumab in elderly patients with AD in real life (Patruno et al, 2021a, Patruno et al, 2021b.…”
Section: Effectiveness and Safety Of Dupilumab For Atopic Dermatitis In The Real Worldmentioning
confidence: 99%
“…The articles searched in PubMed and Google Scholar are shown in Table 1 (Ariëns et al, 2020, Ariëns et al, 2021, Faiz et al, 2019, Fargnoli et al, 2020, Fargnoli et al, 2019, Jang et al, 2020, Jo et al, 2020a, Kreeshan et al, 2021, Matsutani et al, 2020, Nettis et al, 2020b, Nettis et al, 2020c, Olesen et al, 2019, Patruno et al, 2021a, Patruno et al, 2021b, Quint et al, 2020, Ribero et al, 2020, Sears et al, 2020, Tauber et al, 2019, Uchida et al, 2021, Uchida et al, 2019. Patruno et al reported the effectiveness and safety of dupilumab in elderly patients with AD in real life (Patruno et al, 2021a, Patruno et al, 2021b. Halling et al reported a systematic review and meta-analysis of real-world data on the efficacy and safety of dupilumab in patients with AD (Halling et al, 2021).…”
Section: Effectiveness and Safety Of Dupilumab For Atopic Dermatitis In The Real Worldmentioning
confidence: 99%
“…Apart from the appearance of lichenified eczema at the antecubital and popliteal fossa, AD can present in the elderly with atypical clinical phenotypes such as prurigo nodularis, nummular eczema, or generalized eczema more frequently than in other age groups. On the other hand, older patients often suffer from asteatosis and pruritus due to physiologic skin aging and comorbidities, for which they take medications that may worsen pruritus and dry skin [22].…”
Section: Ultraviolet (Uv) Radiation and Skin Barrier Dysfunctionmentioning
confidence: 99%